The Handless Maiden : Moriscos and the Politics of Religion in Early Modern Spain - Perry, Mary Elizabeth, 1937- (Book collections on Project MUSE., 2005)
"In 1502, a decade of increasing tension between Muslims and Christians in Spain culminated in a royal decree that Muslims in Castile wanting to remain had to convert to Christianity. Mary Elizabeth Perry uses this event as the starting point for a remarkable exploration of how Moriscos, converted Muslims and their descendants, responded to their increasing disempowerment in sixteenth- and early-seventeenth-century Spain. Stepping beyond traditional histories that have emphasized armed conflict from the view of victors, The Handless Maiden focuses on Morisco women. Perry argues that these women's lives offer vital new insights on the experiences of Moriscos in general, and on how the politics of religion both empowers and oppresses." "Drawing on archival documents, legends, and literature, Perry shows that the Moriscas carried out active resistance to cultural oppression through everyday rituals and acts. For example, they taught their children Arabic language and Islamic prayers, dietary practices, and the observation of Islamic holy days. Thus the home, not the battlefield, became the major forum for Morisco-Christian interaction. Moriscas' experiences further reveal how the Morisco presence provided a vital counter-identity for a centralizing state in early modern Spain. For readers of the twenty-first century, The Handless Maiden raises urgent questions of how we choose to use difference and historical memory."--Jacket